Self-Concept in Working with Physical Disabilities - Amelia Sekar Hani (Journal of Disability, 2022)
This study aims to determine the self-concept that is formed in physical disabilities who work and is included in qualitative research. The technique of collecting data is in-depth interviews. The interview guide in this study refers to aspects that affect self-concept. The informants in this study were six adults with physical disabilities who were already working. The self-concept that is formed is analyzed from the aspects that affect the self-concept. The data analysis technique used is a descriptive qualitative analysis technique proposed by Miles and Huberman, which is presented in the form of tables and schematics. This study found that aspects of self-concept influence each other in the process of forming self-concept. This study concludes of this study is that the self-concept that is formed in physical disabilities who work is in the category of positive self-concept Keywords: physical disability, self-concept, work